The Effect of Airway Pressure Release Ventilation on Pulmonary Catheter Readings: Specifically Pulmonary Capillary Wedge Pressure in a Swine Model - Ahmad M. Slim; Shaun Martinho; Jennifer Slim; Eddie Davenport; Luadino M. Castillo-Rojas; Eric A. Shry (Anesthesiology Research and Practice)
Background. Airway pressure release ventilation (APRV) is a mode of mechanical ventilation that theoretically believed to improve cardiac output by lowering right atrial pressure. However, hemodynamic parameters have never been formally assessed. Methods. Seven healthy swine were intubated and sedated. A baseline assessment of conventional ventilation (assist control) and positive end-expiratory pressure (PEEP) of 5 cm H2O was initiated. Ventilator mode was changed to APRV with incremental elevations of CPAP-high from 10 to 35 cm H2O. After a 3-to-5-minute stabilization period, measurements of hemodynamic parameters (PCWP, LAP, and CVP) were recorded at each level of APRV pressure settings. Results. Increasing CPAP caused increased PCWP and LAP measurements above their baseline values. Mean PCWP and LAP were linearly related (LAP = 0.66∗PCWP + 4.5 cm H2O, 𝑅2=0.674, and 𝑃<.001) over a wide range of high and low CPAP values during APRV. With return to conventional ventilation, PCWP and LAP returned to their baseline values. Conclusion. PCWP is an accurate measurement of LAP during APRV over variable levels of CPAP. However, PCWP and LAP may not be accurate measurements of volume when CPAP is utilized.